"It is Difficult to Get Permission During Working Hours": Qualitative Analysis Of Treatment Compliance Of Hypertension Patients With Worker Status At The Elderly Posyandu - selvi_ardani Ardani; Dwi Linna Suswardanny (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Hypertension is a major non-communicable disease that is often undiagnosed and can lead to serious complications. Pucangan Village has the highest number of hypertension cases in the Kartasura Community Health Center area, highlighting the need to improve management, especially among working patients. This study aimed to explore factors influencing medication adherence in working hypertensive patients using a descriptive qualitative approach. A total of 22 informants were involved, including 10 primary informants (5 adherent and 5 non-adherent patients) and 12 triangulation informants (10 family members and 2 Posyandu cadres/officers). Data were collected through in-depth interviews and analyzed qualitatively through transcription, reduction, coding, categorization, and theme development, with validity ensured by source triangulation. The results show that Posyandu serves as an initial screening point, with referrals to health centers for further care. Medication adherence is influenced by workload, time constraints, patient perceptions, and irregular medication use, while family support and the role of Posyandu cadres are important in improving adherence.